Green Halal Business Model: Integrating Maqasid al-Shari'ah into Circular Economy Practices for Sustainable Competitive Advantage - Ade Khadijatul Z. Harahap; Rahmat (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study aims to propose an integrative framework of the "Green Halal" business model that synergizes the dimensions of Maqasid al-Shari'ah with the principles of a circular economy to achieve sustainable competitive advantage. The urgency of this research is based on the low waste recycling rate in Indonesia, which only reaches 10-12%, amidst the rapid growth of the national halal industry Method: Using an exploratory qualitative approach through literature review and content analysis, this study analyzes how Islamic noble values are transformed into modern operational strategies. Results: The results of the study indicate that the integration of the dimensions of Hifz al-Bi'ah (environmental protection) and Hifz al-Mal (protection of wealth through efficiency) can transform wasteful linear production patterns into regenerative circular systems. The implementation of Digital Halal Traceability technologies such as Blockchain and IoT is identified as a key driver in ensuring supply chain transparency while minimizing the carbon footprint. The novelty of this research lies in the use of Maqasid al-Shari'ah as an operational ethical compass that positions the circular economy not merely as a management trend, but as a theological obligation. Conclusion: This study concludes that the "Green halal" model provides a competitive advantage through cost leadership and value differentiation for increasingly environmentally conscious consumers